2021
DOI: 10.1002/ppul.25655
|View full text |Cite
|
Sign up to set email alerts
|

High flow nasal cannula versus standard low flow nasal oxygen during flexible bronchoscopy in children: A randomized controlled trial

Abstract: Background: Hypoxemia is the most frequent complication of fiberoptic bronchoscopy (FB) in children. Guidelines recommend oxygen supplementation and conventional nasal prongs (NC) are used for this purpose. The aim of this study was to evaluate if the use of high-flow nasal cannula therapy (HFNC) in children undergoing FB result in a lower incidence of hypoxemia than standard oxygen administration.Methods: Patients aged 1 month-16 years undergoing elective FB were included in a prospective randomized controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 28 publications
0
44
0
Order By: Relevance
“…21203/rs.3.rs-989822/v1], two dental trials [23,40] and one endovascular trial [25]. Three of the trials studied children [21,23,26], one each in cardiology [21], bronchoscopy [26] and dental procedures [23] with a total sample size of 329 patients. Four trials assessed patients at high risk of developing hypoxaemia [9,22,35,37] in one [38] and a combination of low-flow nasal oxygen and bite block oxygen insufflation in one [37].…”
Section: Resultsmentioning
confidence: 99%
“…21203/rs.3.rs-989822/v1], two dental trials [23,40] and one endovascular trial [25]. Three of the trials studied children [21,23,26], one each in cardiology [21], bronchoscopy [26] and dental procedures [23] with a total sample size of 329 patients. Four trials assessed patients at high risk of developing hypoxaemia [9,22,35,37] in one [38] and a combination of low-flow nasal oxygen and bite block oxygen insufflation in one [37].…”
Section: Resultsmentioning
confidence: 99%
“…Abulebda et al 1 found that the incidence of transient hypoxemia in infants was significantly higher than that in toddlers and children (46%, 6%, and 7%, respectively), so the clinical application of FB in infants was limited to some extent. We read with interest the article of Sharluyan et al, 2 which confirmed that high‐flow nasal cannula (HFNC) was safe, well tolerated, and effective in children's soft bronchoscopy, especially in children requiring bronchoalveolar lavage (BAL). Due to the lack of HFNC in our hospital, we improved T‐piece resuscitators (TPR) for infant bronchoscopy based on the characteristics of HFNC.…”
Section: Figurementioning
confidence: 91%
“…Abulebda et al 1 found that the incidence of transient hypoxemia in infants was significantly higher than that in toddlers and children (46%, 6%, and 7%, respectively), so the clinical application of FB in infants was limited to some extent. We read with interest the article of Sharluyan et al, 2 pressure artificial respiration of premature infants and newborns. The current instructions for TPR have clearly indicated that it can be used in infants ranging from 450 g to 10 kg.…”
mentioning
confidence: 99%
“…Hypoxemia is the most frequent complication, and the risk in patients undergoing this procedure is approximately 26–69.1%, due to the different choices of anesthesia and inconsistent indicators for evaluating hypoxemia [ 12 , 20 , 21 , 22 , 23 , 24 , 25 ]. Many patients could not tolerate a bronchoscopic procedure without sedation for anxiety and intense stimulation.…”
Section: Introductionmentioning
confidence: 99%